Realist vision - Brooks, Peter, 1938- (Yale University Press, 2005)
Realist Vision explores the claim to represent the world "as it is". Peter Brooks takes a new look at the realist tradition and its intense interest in the visual. Discussing major English and French novels and paintings from the nineteenth and twentieth centuries, Brooks provides a lively and perceptive view of the realist project. Centering each chapter on a single novel or group of paintings, Brooks examines the "invention" of realism beginning with Balzac and Dickens, its apogee in the work of such as Flaubert, Eliot, and Zola, its continuing force in James and modernists such as Woolf. He considers also the painting of Courbet, Manet, Caillebotte, Tissot, and Lucian Freud, and such recent phenomena as "photorealism" and "reality TV."